Epidemiology of Pestivirus H in Brazil and Its Control Implications - Bauermann, Fernando V.; Ridpath, Julia F. (Frontiers in Veterinary Science, 2021)
Along with viruses in the Pestivirus A (BVDV1) and B species (BVDV2), members of the Pestivirus H are mainly cattle pathogens. Viruses belonging to the Pestivirus H group are known as HoBi-like viruses (HoBiPev). Genetic and antigenic characterization suggest that HoBiPev are the most divergent pestiviruses identified in cattle to date. The phylogenetic analysis of HoBiPev results in at least five subgroups (a to e). Under natural or experimental conditions, calves infected with HoBiPev strains typically display mild upper respiratory signs, including nasal discharge and cough. Although BVDV1 and BVDV2 are widely distributed and reported in many South American countries, reports of HoBiPev in South America are mostly restricted to Brazil. Despite the endemicity and high prevalence of HoBiPev in Brazil, only HoBiPev-a was identified to date in Brazil. Unquestionably, HoBiPev strains in BVDV vaccine formulations are required to help curb HoBiPev spread in endemic regions. The current situation in Brazil, where at this point only HoBiPev-a seems present, provides a more significant opportunity to control these viruses with the use of a vaccine with a single HoBiPev subtype. Despite the lack of differentiation among bovine pestiviruses by current BVDV tests, the reduced genetic variability of HoBiPev in Brazil may allow reliable identification of cases within the region. On the other hand, introducing foreign ruminants, biologicals, and genetic material to South America, especially if it originated from other HoBiPev endemic countries, should consider the risk of introducing divergent HoBiPev subtypes.